2021
DOI: 10.1523/jneurosci.2074-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

Single-Nucleus RNA-Seq Reveals Dysregulation of Striatal Cell Identity Due to Huntington's Disease Mutations

Abstract: Huntington's disease (HD) is a dominantly inherited neurodegenerative disorder caused by a trinucleotide expansion in exon 1 of the huntingtin (HTT) gene. Cell death in HD occurs primarily in striatal medium spiny neurons (MSNs), but the involvement of specific MSN subtypes and of other striatal cell types remains poorly understood. To gain insight into cell type-specific disease processes, we studied the nuclear transcriptomes of 4524 cells from the striatum of a genetically precise knock-in mouse model of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 65 publications
3
45
0
Order By: Relevance
“…Striatal transcriptional dysregulation is one of the hallmarks of HD [36][37][38] and specific gene expression changes using qRT-PCR have also been reported in the HD hypothalamus [39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…Striatal transcriptional dysregulation is one of the hallmarks of HD [36][37][38] and specific gene expression changes using qRT-PCR have also been reported in the HD hypothalamus [39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…Drd1 is downregulated in dSPNs of HD models (Fig. 5A,C,D), reflecting their loss of transcriptomic identities 36 . However, another strong marker of dSPNs, Ebf1 , a well-known factor contributing to dSPNs differentiation 37, 38 , was upregulated in dSPNs (i.e., M-D1 and S-D1, Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Secondly, they deciphered a transcriptional gradients coding for both the anatomical location of a given SPNs, as well as its compartmental identity. Additionally, most studies confirmed the existence of transcriptionally defined eSPNs or eSPN-like D1-Pcdh8-neurons (Gokce et al, 2016 ; Saunders et al, 2018 ; Anderson et al, 2020 ; Malaiya et al, 2020 ; Stanley et al, 2020 ), D1/D2-SPNs (Gokce et al, 2016 ; Martin et al, 2019 ; Anderson et al, 2020 ; Stanley et al, 2020 ) and exopatch neurons (Smith et al, 2016 ; Martin et al, 2019 ; Figure 1B ).…”
Section: Advances and Limitationsmentioning
confidence: 91%
“…The gene set to identify dSPNs includes, for example, Drd1a (the gene coding for the D1 receptor), Tac1 and Isl1 , whereas the set to identify iSPNs includes Drd2 (coding for the D2 receptor), Adora2a , Penk , Gpr6 , Gpr52 , and SP9 . These sets enabled a discrete and robust separation of the “classical” SPNs, and similar ones were used in subsequent studies (Ho et al, 2018 ; Saunders et al, 2018 ; Martin et al, 2019 ; Malaiya et al, 2020 ; Stanley et al, 2020 ). Secondly, it also reported a small group of D1/D2 SPNs.…”
Section: Transcriptional Profiles Reveal a Code For Striatal Heterogeneity And New Types Of Spnsmentioning
confidence: 99%